INCUBATOR IDEAS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Sylvestre Woumbondi, Maroua, Cameroon: 'We would like to to share with you our experience at this college with artificial incubation of chicken and guinea fowl eggs. The type of incubator we used, which is made locally, allows us to obtain a...